Novel insights on saccharin- and acesulfame-based carbonic anhydrase inhibitors: design, synthesis, modelling investigations and biological activity evaluation - Paolo Guglielmi; Giulia Rotondi; Daniela Secci; Andrea Angeli; Paola Chimenti; Alessio Nocentini; Alessandro Bonardi; Paola Gratteri; Simone Carradori; Claudiu T. Supuran (Taylor & Francis Group, 2020)
A large library of saccharin and acesulfame derivatives has been synthesised and evaluated against four isoforms of human carbonic anhydrase, the two off-targets hCA I/II and the tumour related isoforms hCA IX/XII. Different strategies of scaffold modification have been attempted on both saccharin as well as acesulfame core leading to the obtainment of 60 compounds. Some of them exhibited inhibitory activity in the nanomolar range, albeit some of the performed changes led to either micromolar activity or to its absence, against hCA IX/XII. Molecular modelling studies focused the attention on the binding mode of these compounds to the enzyme. The proposed inhibition mechanism is the anchoring to zinc-bound water molecule. Docking studies along with molecular dynamics also underlined the importance of the compounds flexibility (e.g. achieved through the insertion of methylene group) which favoured potent and selective hCA inhibition.